2018
DOI: 10.21101/cejph.a5043
|View full text |Cite
|
Sign up to set email alerts
|

Child and parental physical activity: Is there an association with young children activity?

Abstract: Children accumulated more steps on weekdays than at the weekend (F = 18.58, p < 0.001, η = 0.27), while boys presented higher PA than girls (F = 12.42, p = 0.001, η = 0.20), and accomplished the recommended daily PA, in contrast to girls. Mothers and fathers presented similar PA (p = 0.67, η = 0.004), with more steps on weekdays than at the weekend (F = 9.22, p = 0.004, η = 0.16). However, their PA was significantly lower than the recommended. Finally, there were no statistically significant associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
4
4
2
1
Order By: Relevance
“…Consistently with other studies [27,46,47], it was observed that the boys were more physically active than the girls. Although it is difficult to increase the PA of girls, especially during adolescence, it seems that enjoyment and social support for PA are important mediators of adolescent girls' PA [48].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently with other studies [27,46,47], it was observed that the boys were more physically active than the girls. Although it is difficult to increase the PA of girls, especially during adolescence, it seems that enjoyment and social support for PA are important mediators of adolescent girls' PA [48].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the Groningen Expert Center for Kids with Obesity (GECKO) study, which was based on objectively measured PA in children aged 4-7 years and self-reported PA in parents [27], confirmed a significant PA relationship only between mothers and daughters (not sons). This was analogous to a Greek study on five-to-eight-year-old children that reported that fathers' PA was mainly related to their sons' PA [47]. In the current study, we noticed stronger parent-child associations in children younger than eight years, whereas the SOPHYA study reported the strongest parent-child relationship in children aged 10-12 years [30].…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, ST for 2-5-year-old children should be limited to one hour per day [15,16]. Nevertheless, despite the aforementioned published guidelines, today's young children have been found to be both physically inactive [7,[17][18][19]] and heavily exposed to screens [7,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Participating parents in a study by Joseph et al [ 144 ] acknowledged that taking their child to specific locations, such as the park, could help facilitate more PA and parents have previously expressed the desire for more opportunities for parental involvement [ 145 ]. Parental PA and sport participation influences offspring PA [ 147 , 148 ] and MVPA [ 149 ]. A longitudinal study has shown parental PA to be associated with offspring PA from childhood until middle age [ 150 ].…”
Section: Discussionmentioning
confidence: 99%